WHO IS MORE DOMINANT IN HUSBAND AND WIFE PURCHASE DECISIONS? - Sutisna, Sutisna (Yayasan Education and Social Center, 2025)
Purchasing decisions between spouses are often a problem in the family. Who is more dominant in purchasing decisions between husband and wife is influenced by many variables. This study aims to investigate the role of variables such as the couple's marital age, occupation, income, and the price paid for marriage. The research was conducted in Banten province with a total of 215 Muslim respondents. The data analysis method uses cross-tabulation analysis and logistic regression to analyse the categorical data. The results of the study showed that the marital status, employment, and income of couples did not have a significant effect on the dominance of husbands in the purchase decisions of husbands and wives. The larger amount of money that the husband brings into the marriage has a positive and significant impact on the husband's dominance in the couple's purchasing decisions. Husbands who bring more value into marriage will dominate the purchase decision by 1.9 times compared to husbands who bring less value into marriage.